Risk Management Nexus by Pakistan and China to Combat Novel Corona Virus in the Light of Actor-Network Theory - Wajahat Ali Ghulam; Shujahat Ali; Waqas Ali (Logistic and Operation Management Research (LOMR), 2023)
This research paper presents the COVID-19 situation and early control measures the Government of Pakistan took. The first coronavirus case was confirmed in Pakistani on February 25, 2020. To avoid any disastrous situation, The Pakistani Government has done everything possible to reduce the number of coronavirus cases across its provinces as much as possible up until now. We have investigated Pakistan's thorough response compared to the neighboring country China. The researcher performed trend analysis based on the data from the official COVID-19 record website of the government of Pakistan and GitHub - JHU CSSE for China. The data indicates a decline in COVID-19 cases and a high recovery rate in Pakistan. No double-figure positive cases from the last few weeks are recorded as of March 16, 2023. We have compared the strategies of Pakistan to combat COVID-19 with China as it shut down its border from March 2020 to October 2023 to protect its social system. On the other hand, Pakistan didn't shut down the border completely during COVID-19. According to the findings, we can state that no large-scale death toll has been recorded in Pakistan. Pakistan maintains its survival during COVID-19 due to the efficient cooperation of the stakeholders in the light of the Actor-Network Theory. Despite the lack of effective antiviral treatment, Pakistan took proactive steps to combat coronavirus. Furthermore, the lockdowns and other preventative measures implemented by the provincial governments led to decreased COVID-19 cases in the nation. The fact that only 4% of Pakistan's population is over 60 indicates less risk of a COVID-19 outbreak leading to a large-scale death toll. Despite the lack of effective antiviral treatment, Pakistan took proactive steps to combat coronavirus.